Analisis RULA dan Nordic Body Map pada Karyawan di Assembly Section Komponen Sayap Pesawat A350 pada PT. XYZ - Aldian, M. Nabil Daffany; Sari, Rizqi Novita (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
PT. XYZ is a company specializing in the manufacture of aircraft components. Within the spirit division (responsible for developing aircraft wing components), specifically in the A350 aircraft wing assembly section, employees have been observed to suffer from work-related fatigue and physical complaints, consequently impacting production process performance. This study, therefore, aims to analyze the RULA (Rapid Upper Limb Assessment) and Nordic Body Map (NBM) assessment results of employees involved in the A350 aircraft wing component production within the assembly section. Employing a quantitative descriptive research methodology, the study found the NBM assessment for the riveting and drilling tasks yielded a total score of 72 for employee 1, indicating a high risk of developing musculoskeletal disorders (MSDs), necessitating immediate intervention. Employee 2 received a total NBM score of 54, representing a moderate risk of MSDs, suggesting that future action may be necessary. The RULA assessment for the same riveting and drilling tasks resulted in a Grand Score of 5 for employee 1 (high risk of MSDs), requiring immediate corrective action, and a Grand Score of 3 for employee 2 (moderate risk of MSDs), recommending short-term improvements. The proposed improvement strategy utilizes the 5W + 1H method, focusing on redesigning workstations, modifying employee work postures, and implementing regular stretching exercises during work breaks. Keywords: Musculoskeletal Disorders, Nordic Body Map, Production, RULA